Span of control, transaction costs, and the structure of production chains - Tomoo Kikuchi; Kazuo Nishimura; John Stachurski (Theoretical Economics, 2018)
This paper builds coordination costs, transaction costs, and other aspects of the theory of the firm into a production chain model with an infinite number of ex ante identical producers. The equilibrium determines prices, allocations of productive tasks across firms, firm sizes, and the number of active firms. These prices and allocations match several stylized facts on firm boundaries, vertical integration, and division of the value chain.
Keywords: C62; C63; L11; L16; 330; Span of control; firm boundaries; fragmentation; production chains